Metastatic pancreatic carcinoma masquerading as cystic lung disease: a rare presentation. Issue 5 (11th June 2017) - Stern, Emily; Huseini, Taha; Kuok, YiJin; Lake, Fiona
Abstract : This 52‐year‐old male ex‐smoker presented with a six‐month history of progressive breathlessness and weight loss. He deteriorated acutely, and was admitted with severe type 1 respiratory failure. Apart from diffuse coarse crackles on chest auscultation, physical examination was unremarkable. High‐resolution computed tomography (HRCT) showed diffuse cystic changes throughout the lungs. A diagnosis of pulmonary Langerhans cell histiocytosis (PLCH) was considered. Further workup identified a coincidental pancreatic lesion of uncertain significance, which remained indeterminate on magnetic resonance imaging (MRI) and on positron emission tomography (PET). Transbronchial biopsy revealed enteric differentiated adenocarcinoma exhibiting lepidic spread, and autopsy later confirmed primary pancreatic malignancy. This case demonstrates that metastatic pancreatic malignancy can present with severe respiratory failure and masquerade as cystic lung disease. Abstract : This case describes a 52‐year‐old gentleman who presented with acute type 1 respiratory failure and diffuse cystic change on high‐resolution computed tomography (HRCT). Transbronchial biopsy revealed enteric differentiated adenocarcinoma exhibiting lepidic spread, and autopsy confirmed a pancreatic primary. This case demonstrates that pancreatic malignancy can present with cystic lung disease and acute respiratory failure.